2002
DOI: 10.1046/j.1442-2050.2002.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rigiflex balloon dilatation in 12 children with achalasia: a 6-month prospective study showing weight gain and symptomatic improvement

Abstract: Achalasia cardia is a disease of adolescents and is rare in children. In total, 12 children with primary achalasia, with a mean age of 10.8 +/- 2 years, were prospectively evaluated for the efficacy of a 30-mm-diameter Rigiflex balloon for relief of symptoms and weight gain after 1 and 6 months of follow up. The 12 children were evaluated and treated for achalasia, with pneumatic balloon dilatation, from January 1998 to December 2000. They were studied for basal, 1-, and 6-month post-dilatation composite sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…9,[31][32][33][34] Although there are reported perforation rates of 4% to 12% in adult patients, [10][11][12][13][14][15][16][17][18][19][20][21][22] no perforations have been documented in pediatric patients. [23][24][25][26][27][28][29][30] In our series, we did not observe serious complications, only self-limited postprocedural pain in 11% of patients.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…9,[31][32][33][34] Although there are reported perforation rates of 4% to 12% in adult patients, [10][11][12][13][14][15][16][17][18][19][20][21][22] no perforations have been documented in pediatric patients. [23][24][25][26][27][28][29][30] In our series, we did not observe serious complications, only self-limited postprocedural pain in 11% of patients.…”
Section: Discussionmentioning
confidence: 50%
“…A review of the literature shows that PD is successful in the majority of reported pediatric series, with success rates of 45% to 90%; this method has not gained universal acceptance in children. [23][24][25][26][27][28][29][30] Azizkhan et al 25 and Nakayama et al 26 reported that PD was unsuccessful in children younger than 9 years of age and technically difficult to perform in children younger than 5 years of age. This is the largest prospective study in pediatric achalasia aimed at evaluating the efficacy and safety of PD as well as factors predicting outcome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…96,97 Pneumatic dilation for achalasia has been compared with surgical myotomy in several small reviews. [82][83][84][85][86][87][88] Most conclude that surgery offers a more durable benefit, but pneumatic dilation is effective and is a reasonable first-line therapy in children. Argon plasma coagulation using a 2.3-or 1.5-mm probe was used in a series of 13 pediatric patients, mainly for bleeding (n ϭ 12) indications (eg, ulcers, hemangioma, eroding tumor mass).…”
Section: Efficacy and Comparative Studiesmentioning
confidence: 97%
“…[82][83][84][85][86][87][88] Pediatric-specific pneumatic dilation balloons are not produced, and standard 30-, 35-, and 40-mm polyurethane balloons are used.…”
Section: Therapy For Esophageal Stricturesmentioning
confidence: 99%